Design and synthesis of a series of OFF-ON near infrared fluorescent probes for nucleic acid in aqueous solution. (15th September 2021) - Zhu, Ming-Sen; Zhang, Xiao-Qing; Wei-Ma; Sun, Ru; Xu, Yu-Jie; Ge, Jian-Feng
Graphical abstract: Abstract: Five cyanine dyes (6a-e ) with aza units were prepared by the reaction of pyridinum or quinolinium with suitable aldehydes. They present several remarkable features including large Stokes shift (235–282 nm), long emission wavelength (640–698 nm) and excellent selectivity. Moreover, probes 6a-b display obvious and sensitive fluorescent response to DNA and RNA in aqueous solution, and the quantum yield of probe 6a response to RNA increases from 0 to 8.9%. More importantly, probes 6c and 6e can effectively avoid DNA interference and only respond to RNA in aqueous solution. In addition, laser confocal cell experiment has showed that probe 6b can image the nucleolus of nucleic acids in HeLa cells.